Pengaruh Inovasi Produk dan Promosi Terhadap Kinerja Pemasaran UMKM di Dusun Gunung Batu, Kecamatan Sumberejo, Kabupaten Tanggamus, Lampung - Meli Agustina; Vicky F Sanjaya; Hasbullah Hasbullah (Jurnal Manajemen dan Bisnis (JMB), 2022)
ABSTRACKProduct innovation and promotion is one indicator to measure the success and success of managing a business. Because product innovation and promotion are variables that are believed to be able to improve marketing performance, especially for micro, small and medium enterprises (MSMEs). The purpose of this study was to directly examine the product innovation and promotion variables on marketing performance to employees or owners of MSMEs. The number of samples included in this study was 34 and Smart PLS 3 was used as an analytical tool. The results of this study indicate that product innovation and promotion have a positive and significant effect on marketing performance.Keywords: Product Innovation and Promotion on Marketing Performance